J. G. Montes Cala, M. Sánchez Ortiz de Landaluce, R. J. Gallé Cejudo y T. Silva Sánchez, Studia Hellenistica Gaditana I. Teócrito, Arato, Argonáuticas Órficas, Cádiz, Universidad de Cádiz, 2003 (Minerva. Revista de Filología Clásica, 2019)
Reseña de J. G. Montes Cala, M. Sánchez Ortiz de Landaluce, R. J. Gallé Cejudo y T. Silva Sánchez, Studia Hellenistica Gaditana I. Teócrito, Arato, Argonáuticas Órficas, Cádiz, Universidad de Cádiz, 2003